Frequency of Hyponatremia in Patients with Intracerebral Hemorrhage (Medical Forum Monthly, 2024)
Objectives:To determine the frequency of hyponatremia in patients having intracerebral hemorrhage (ICH) at Nishtar Hospital Multan.Study Design:Cross sectional study.Place and Duration of Study: This study was conducted at the Department of Department, NishtarMedical College and Hospital Multan from February 2016 to July 2016.Materials and Methods:In this study, a total of 72 patients with intracerebral hemorrhage were taken who were admitted at Nishtar Hospital Multan. These patients were diagnosed on bases of clinical diagnosis and CT scan report findings such as “CT scan brain plain showing hyper dense area inside brain parenchyma were defined as Intracerebral Hemorrhage”. All these patients were registered in this study, after taking informed consent from their attendants/patients. Patients with clinical and CT scan confirmation of ICH aged more than 30 years of either sex were included in this study.Results: Out of these 72 patients with ICH, 56 (77.8%) were male patients while 16 (22.2%) were female patients and male to female ratio was 3.5:1. Mean age of these ICH patients was 49.21 ± 12.56 years (age rage; 33 – 86 years). Mean age of the male patients was 48.59 ± 11.99 years while that of female patients 51.38 ± 14.61 years (p = 0.438). Of these 72 study cases, 44 (61.1%) were from urban areas while 28 (38.9%) belonged to the rural areas. Twenty two (30.6%) were poor, 33 (45.8%) were middle income and 17 (23.6%) were rich. Mean body mass index of our study cases was 24.92 ± 3.85 kg/m2 (range of BMI; 20.5 to 36.75kg/m2) and 33 (45.8%) were obese. In our study 39 (54.2%) were smokers and all smokers were male patients. Diabetes was present in 33 (45.8%), hypertension in 48 (66.7%), dyslipidemia in 43 (59.7%) and family history in 22 (30.6%). Mean serum sodium level in our study was 137.78 ± 8.77 nmol/L and hyponatremia was noted in 26 (36.1%) patients with intracerbral hemorrhage.Conclusion:Our study provided the measurement in the cadavers with regards to weight of heart and aortic diameter and the thickness of the wall of aorta. It is also concluded that results obtained show significant difference between male and female hearts with regards to these parameters.